Two-stream mixing flow with streamwise vorticity - Mao, Rong Hai (2008)
The aerodynamic characteristics of the single-lobe forced mixer have been extensively examined in the present dissertation. Nine single-lobe models with different parameters and geometry configurations were designed and fabricated. Penetration angles, lobe wavelengths, trailing edge configurations and modifications vary from case to case. Flat plate (to simulate plane free shear layer) and convoluted plate (to generate normal K-H vortex without streamwise vortex) have also been tested as baselines for comparison. Two velocity ratios, i.e., r =1: 1 and 0.4: 1 and Reynolds numbers (based on the wavelength of the basic single-lobe forced mixer) ranged from 9,200 to 40,000 have been chosen and tested.